PERANCANGAN DAN ANALISIS JAW GRIPPER PADA STASIUN PERAKITAN MODULAR SISTEM PRODUKSI MENGGUNAKAN METODE FAILURE MODE AND EFFECTS ANALYSIS - Bryan Willynata; Agus Halim; Didi Widya Utama (Jurnal Mitra Teknik Industri, 2026)
This study aims to design and analyze the jaw gripper on the Modular Production System (MPS) assembly station. This study was conducted by analyzing using Failure Mode and Effect Analysis (FMEA). The design serves to adjust the shape and size of the work object in the form of a cap, piston, spring and cylinder body so that the assembly process can run smoothly. The design was made using Fusion 360 software and the production process used PLA+ material with a 3D printing method. Strength analysis was carried out using the static stress method in Fusion 360 software with safety factor parameters VonMises stress, Displacement and Strain. The minimum safety factor value obtained for the cap is 4,795, the spring is 2,485, and the piston is 6,17, so that the analysis results indicate that the design is in a safe state. The stress and deformation values obtained are also still within the permitted limits. The calculation of the minimum gripping force value is 0,56 N and the holding force is 0,22 N. Failure Mode and Effect Analysis analysis is used to help prevent potential system failures. The research results show that the jaw gripper design is able to increase the reliability, efficiency and safety of the assembly system.